Measurıng Consumer-Based Brand Equıty: Evıdence From Indonesıa's Athletıc Footwear Market - Erie Awalil Fakhri (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
Premium athletic footwear products provided by global apparel brands instead of cheap and generic products due to recent trends such as athleisure is becoming trend in Indonesia in the last decades. This occurring phenomenon creates new opportunities for multinational apparel brands to further explore the Indonesian market. Therefore, it is crucial for such companies to understand how Indonesians view sports brands by measuring brand equity and what factors influence it. This study aims to examine the effects of brand awareness, brand loyalty, brand association and perceived quality on consumer-based brand equity. The research objects of this study are Indonesians who live in Java and have purchased athletic footwear products from multinational sportswear brands. A total of 275 data was collected using mail survey method. Data analysis was performed using Partial Least Square (PLS) with the SmartPLS software. The study revealed that brand loyalty and brand association influence consumer-based brand equity, while brand awareness and perceived quality did not obtain enough evidence to support their influence on consumer-based brand equity. Practical implications also discussed in this article.